Valuing Companies Through Environment, Social, Governance: The Role of Company Reputation and Financial Performance as Mediating Variables in Companies Listed on the IDX - Utami, Reistiawati; Zuyyina, Z.; Firmansyah, Aditia; Muhtadin, Yulian (Manunggal Halim Jaya, 2025)
The ESG framework is an important sustainability strategy that companies can easily integrate into their management practices. This framework supports responsible governance and aims to create long-term value. This study will analyze how ESG components affect corporate performance, reputation, and overall company value. Although previous research has provided various findings on the relationship between ESG and corporate value, this study focuses on clarifying these inconsistencies. We analyzed 39 public companies that disclosed their ESG performance from 2019 to 2023. Using statistical analysis with Smart PLS Version 4, we found that environmental and governance aspects significantly influence financial performance. In addition, our observations show that corporate governance, reputation, and financial performance play an important role in increasing company value. Specifically, this study proves that financial performance acts as an intermediary variable between the environment and governance on company value. This study provides valuable implications for managers, emphasizing the importance of promoting corporate governance, financial performance, and reputation. By focusing on these key areas, companies can effectively increase corporate value, achieve sustainability, and build corporate reputation.